ANALISIS PENGGUNAAN TATA BAHASA DAN PEMEROLEHAN BAHASA KEDUA BAHASA INGGRIS PADA MAHASISWA THAILAND - Minkhatunnakhriyah Minkhatunnakhriyah; Fahriany Fahriany; Albiansyah Albiansyah (Universitas Dian Nuswantoro, 2021)
Abstract: This paper aims to determine the types of grammar usage and to describe the acquisition of English as a second language among Thai students. The method used was a qualitative paradigm and the data sources were taken from interviews. The interview instrument was used to obtain the data in the form of English text production, which was used to identify and to classify the types of grammar elements and information on how informants acquire the language. This study results in variations in the use of grammar elements namely simple present tense, simple past tense, degree of comparison, noun phrases, and auxiliary verbs. The results of the interview show that the process of mastery of a second language was obtained through watching films in English or films with English subtitles, reading novels in English, and listening to English songs. Keywords: English Grammar; Second Language Acquisition; Speaking